Memaknai Pembangunan dalam Perspektif Kesejahteraan Sosial - Purwanto, Agus Budi (Sosio Informa, 2013)
The tantrums concept may be a new thing for most parents, in fact this behavior is common to the parents in parenting. Tantrum behavior is normal behavior for children aged 15 months - 6 years, even in the form of aggressive behavior. Therefore parents need not worry if their children have it. This behavior is not a permanent behavior. This behavior arises because children feels discomfort due to several reasons; e.g. hunger, sleepiness, pain, unfulfilled desire, inappropriate response, attacked or criticized, deprived, meet with strangers, etc. Inconsistent parenting also contributes to the emersion of this behavior, including overindulges and comply the children pretension. Such behavior is normal in nature. Nevertheless, parents need to respond it appropriately. If not, it will affect the children behavior development. This paper aims to provide an understanding of tantrums behavior, its grounding theory, the cause, as well as the way to deal with children who have tantrums.